Algoritma Pemanas Air Kolam Pemandian Berbasis Mikrokontroler Atmega8535 - Awallu, Niam Yusuf; Aprilianto, Tria (Jurnal Ilmiah Teknologi Informasi Asia, 2011)
In modern era, technology is growing rapidly, especially on the water heater. There are many kind of water heater. There is a water heater using solar power, water heaters use gas energy and water heaters use electricity, but of those tools are still some deficiencies or weaknesses of each. To overcome this, the writer tried to take advantage of the sophistication of the microcontroller ATMEGA8535 to create an automated bath water heater.